Selective Serotonin Reuptake Inhibitor (SSRI) Antidepressants, Prolactin and Breast Cancer - Ashbury, Janet; Lévesque, Linda; Beck, Patty; Aronson, Kristan (Frontiers in Oncology, 2012)
Selective serotonin reuptake inhibitors (SSRIs) are a widely prescribed class of anti-depressants. Laboratory and epidemiologic evidence suggests that a prolactin-mediated mechanism secondary to increased serotonin levels at neuronal synapses could lead to a potentially carcinogenic effect of SSRIs. In this population-based case-control study, we evaluated the association between SSRI use and breast cancer risk as a function of their relative degree of inhibition of serotonin reuptake as a proxy for their impact on prolactin levels. Cases were 2,129 women with primary invasive breast cancer diagnosed from 2003-2007, and controls were 21,297 women randomly selected from the population registry. Detailed information for each SSRI prescription dispensed was compiled using the Saskatchewan prescription database. Logistic regression was used to evaluate the impact of use of high and lower inhibitors of serotonin reuptake and duration of use, as well as to assess the effect of individual high inhibitors on the risk of breast cancer. Exclusive users of high or lower inhibitors of serotonin reuptake were not at increased risk for breast cancer compared with nonusers of SSRIs (OR = 1.01, CI = 0.88-1.17 and OR = 0.91, CI = 0.67-1.25 respectively), regardless of their duration of use or menopausal status. While we cannot rule out the possibility of a clinically important risk increase (OR = 1.83, CI = 0.99-3.40) for long-term users of sertraline (≥24 prescriptions), given the small number of exposed cases (n=12), the borderline statistical significance and the wide confidence interval, these results need to be interpreted cautiously. In this large population-based case-control study, we found no conclusive evidence of breast cancer risk associated with the use of SSRIs even after assessing the degree of serotonin reuptake inhibition and duration of use. Our results do not support the serotonin-mediated pathway for the prolactin-breast cancer hypothesis.